EFEKTIVITAS PELAKSANAAN PROYEK ECOBRICK TERHADAP LITERASI LINGKUNGAN DAN HASIL BELAJAR FISIKA SISWA - Paskalia, Fransiska Nina (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
Low environmental awareness in society is one of the causes of environmental damage. Environmental literacy is expected to increase learners concern for environmental sustainability. Through ecobrick project learning, it is expected that students environmental literacy and learning outcomes will improve. This study aims to determine the effect of eco brick project implementation on environmental literacy and physics learning outcomes, as well as the relationship between environmental literacy and student learning outcomes. The research method was a pre-experimental design with one group pretest-posttest design. Pretest and posttest were given after and before learning to students. Data were collected through questionnaires to measure environmental literacy and essay questions to measure learning outcomes. This study involved 35 students of class X-4 at SMAN 2 Tenggarong. Based on the paired sample t-test, implementing the ecobrick project shows that environmental literacy is in the high category with a score of 177.3 while learning outcomes about the environment are in the moderate category with a score of 76. Based on the correlation test, environmental literacy on student learning outcomes is in the moderate category with a value of 0.547. Through the results of this study, the eco brick project has the potential to be used as a way to improve environmental literacy and environmental learning outcomes.